Caracterização e quantificação dos compostos polifenólicos e triterpênicos em extratos obtidos a partir das folhas, cascas, frutos e talos de caraipa densifolia mart. - Silveira, Cleoni Virginio da (2010)
Thirty three secondary plant substances were detected in various extracts of the leaves,fruits, stem and bark of Caraipa densifolia Mart. Phenolic compounds were preliminarily identified and quantitated by HPLC-ESI-MS after column chromatography on Sephadex LH-20. Structures of the compounds, purified by semi-preparative HPLC, were further characterized by nano-ESI-MS-MS. The presence of gallic acid, 3,4-dihydroxybenzoic acid, chlorogenic acid (plus an isomer), methyl gallate, p-coumaric acid quinate, epicatechin, procaynidin dimer B2, procyanidin trimer C1, syringic acid, 1, 2, 3, 6-tetragallate glucoside, 1, 3, 4, 6-tetragallate glucoside, corilagin, ellagic acid, methyl ellagic acid rhamnoside, quercetin-3-O-rhamnoside, two apigenin-C-glycosides (vitexin and isovitexin), three further apigenin,cucumerin A cucumerin B e cucumerin C, two luteolin-C-glycosides (orientin and isoorientin) are reported in this species for the first time. In addition, the previously reported following terpenoids, lupeol, lupenone, betulinic acid, betulin, friedelin and a previously non-characterized terpenoid in this species, friedelinol were identified and quantitated by GC-MS. A previously identified sterol was -sitosterol along with stigmasterol in this species for the first time. The vitamins -tocopherol and -tocopherol were also identified in extracts of the leaves of Caraipa species for the first time. Information obtained in this study provide significant contributions to the knowledge of the various formulations commonly used in folk medicine and pharmaceutical industry, representing an important step towards a study of a phytotherapic. The test of antioxidant capacity of extracts FST, FSD and FSH showed a significant activity, thereby obtaining better antioxidant extract FST with IC502, 1mg/mL. The extracts with the best inhibition of Acetylcholinesterase in concentration 2mg/mL applied 2.5 μL. were of FH, TSH, CSH, FSM and FM. The molluscicidal test with the snail Biomphalaria glabrata extracts applied to FH and FM resulted mortality rate 100% for FH in 24 and 60% and 80% for FM in 48 hours